Precipitation behavior of high-Nb containing modified HR3C heat-resistant steels during isothermal aging. Issue 14 (22nd September 2019) - Bai, Jiaming; Yuan, Yong; Zhang, Peng; Yan, Jingbo; You, Caiyin
ABSTRACT: The effect of Cr content on microstructural stability of the modified high-Nb content HR3C austenitic heat-resistant steel has been investigated during thermal aging at 700°C. It was observed that the σ phase precipitated in the 23.5Cr–18Ni–1.7Nb–0.04C–0.1N (wt.%) steel after aging treatment. However, the σ phase was not observed throughout the aging up to 5000 h as the Cr content was reduced from 23.5 to 21.5 wt-%. Experimental results showed that the yield strength of steel with 23.5 wt-% Cr at room temperature increased from 261 to 492 MPa after aging for 5000 h. The strengthening is closely related to the precipitation of σ phase at early stage of aging (500–2000 h). The influence of alloying elements on the formation of σ phase is discussed.